2017
DOI: 10.1016/j.jsxm.2016.12.235
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning of Sexually Compulsive and Non-Sexually Compulsive Men Before and After Watching an Erotic Video

Abstract: Introduction Despite the serious behavioral consequences faced by individuals with sexual compulsivity, related neuropsychological studies are sparse. Aim To compare decision making and cognitive flexibility at baseline and after exposure to an erotic video in sexually compulsive participants and non-sexually compulsive controls. Methods The sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The specifics of this poorer executive functioning include: impulsivity [131,132], cognitive rigidity that impedes learning processes or the ability to shift attention [120,133,134], poor judgment and decision making [130,135], interference of working memory capacity [130], deficits in emotion regulation, and excessive preoccupation with sex [136]. These findings are reminiscent of other behavioral addictions (such as pathological gambling) and the behavior in substance dependencies [137].…”
Section: Resultsmentioning
confidence: 99%
“…The specifics of this poorer executive functioning include: impulsivity [131,132], cognitive rigidity that impedes learning processes or the ability to shift attention [120,133,134], poor judgment and decision making [130,135], interference of working memory capacity [130], deficits in emotion regulation, and excessive preoccupation with sex [136]. These findings are reminiscent of other behavioral addictions (such as pathological gambling) and the behavior in substance dependencies [137].…”
Section: Resultsmentioning
confidence: 99%
“…In line with this consideration, some progress in the examination of neurobiological commonalities with SUDs has been achieved more recently within the domains of sex addiction (SA) and compulsive buying (CB) by analyzing phenomena traditionally investigated in SUDs such as conditioning processes (e.g., Hoffmann, Goodrich, Wilson, & Janssen, 2014 ; Snagowski, Laier, Duka, & Brand, 2016 ), cue reactivity, attentional bias and related neural network activation (e.g., Brand, Snagowski, Laier, & Maderwald, 2016 ; Gola et al, 2017 ; Jiang, Zhao, & Li, 2017 ; Laier, Pawlikowski, & Brand, 2014 ; Laier, Schulte, & Brand, 2013 ; Lawrence, Ciorciari, & Kyrios, 2014 ; Mechelmans et al, 2014 ; Pekal, Laier, Snagowski, Stark, & Brand, 2018 ; Schmidt et al, 2017 ; Seok & Sohn, 2015 ; Starcke, Schlereth, Domass, Schöler, & Brand, 2012 ; Trotzke, Starcke, Pedersen, & Brand, 2014 ; Trotzke, Starcke, Pedersen, Müller, & Brand, 2015 ; Voon et al, 2014 ), or executive functioning ( Derbyshire, Chamberlain, Odlaug, Schreiber, & Grant, 2014 ; Messina, Fuentes, Tavares, Abdo, & Scanavino, 2017 ; Raab, Elger, Neuner, & Weber, 2011 ; Trotzke et al, 2015 ). These studies demonstrated that among those conditions that have not yet been officially recognized in the DSM-5 as BAs, the currently available evidence regarding neurobiological indicators for parallels between substance-related and non substance-related behaviors mainly comes from the areas of IA, SA and CB, which are the focus of the present paper.…”
mentioning
confidence: 99%
“…Dane uzyskane w badaniu wskazały na to, że osoby z kompulsywnymi zachowaniami seksualnymi pod wpływem wskazówek z otoczenia związanych z seksem mają trudności z hamowaniem reakcji oraz gorzej adaptują swoje zachowanie do zmieniających się warunków. W realnym życiu może to mieć odzwierciedlenie w angażowaniu się przez te osoby w ryzykowne zachowania oraz przejawiać się trudnościami z modyfikacją własnych zachowań seksualnych (Messina, Fuentes, Tavares, Abdo, Scanavino, 2017).…”
Section: Problemy W Kontrolowaniu Zachowań Seksualnychunclassified